Hubungan pemakaian alat kontrasepsi IUD dengan tingkat kenyamanan dalam melakukan hubungan seksual - Rilyani Rilyani; Soni Obit Saputra (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Women’s sexual satisfaction after using intrauterine device (IUD) for contraceptionBackground: The results of the 2017 population survey population growth rate in Indonesia (1.49%) and the birth rate is 2.6 / fertile women. The results of the prevalence of family planning in Indonesia in 2013 (65.4%) with injectable contraceptive methods (36%), pills (15.1%), Implants (5.2%), IUDs (4.7%), and tubectomy (2), 2%). In Lampung Province recorded in 2016 the type of IUD reached 8,950.89 CCA (couples of childbearing age) experienced an increase in 2015 from 10,235,542, reaching 911 acceptors.Purpose: To knowing of Women’s sexual satisfaction after using intrauterine device (IUD) for contraceptionMethod: An analytical survey with a cross sectional approach, the population was all women who use intrauterine device (IUD) or others method for contraception with a sample of 91 respondents by random sampling where 71 respondents using an IUD and 20 respondent others method.Results: the average of women’s sexual satisfaction after using intrauterine device (iud) for contraception of 91 respondents means 0.78 standard deviations 0.416 standard errors 0.044 standard errors 0.044 and minimum values max 0-1. The sexual satisfaction means the value is 0.78 standard deviation 0.477 standard error 0.050 min-max 0-1. Chi square statistical test results obtained p value (0.006 <0.05)Conclusion: There was an effect of women’s sexual satisfaction after using intrauterine device (iud) for contraception . Health workers especially nurses can further enhance their skills through the latest literature, training and counseling at every examination of mothers with contraceptive users IUD thus has knowledge of the effects of using an IUD contraceptive.Keywords: Women; Sexual satisfaction; Intrauterine Device (IUD); ContraceptionPendahuluan: Hasil survey penduduk tahun 2017 laju pertumbuhan penduduk di Indonesia 1,49% dan angka kelahiran 2,6 / wanita subur. Hasil prevalensi KB di Indonesia tahun 2013 65,4% dengan metode KB suntik, (36%), pil KB (15,1%), Implant (5,2%), IUD (4,7%), dan MOW (2,2%). BKKBN Provinsi Lampung tahun 2016 KB jenis IUD mencapai 8.950.89 PUS (Pasangan Usia Subur). Mengalami peningkatan di tahun 2015 sebanyak 10.235.542.Tujuan: Mengetahui Hubungan Pemakaian Alat Kontrasepsi IUD Dengan Tingkat Kenyamanan Dalam Melakukan Hubungan SeksualMetode : Penelitian ini menggunakan survei analitik dengan pendekatan cross sectional ada hubungan antara factor resiko dengan efek atau observasi antar variable dilakukan secara bersamaan, dengan sampling 91 responden dengan teknik random sampling.Hasil : Hasil uji statistik chi square didapatkan nilai p value (0,006<0,05) artinya Ho diterima dapat disimpulkan ada hubungan yang bermakna pemakaian alat kontrasepsi IUD dengan tingkat kenyamanan melakukan hubungan seksual. OR didapat dapat 4.105 yang artinya responden yang memakai alat kontrasepsi IUD memiliki resiko lebih besar 5.105 kali ada masalah tingkat kenyamanan melakukan hubungan seksual di bandingkan dengan responden yang tidak menggunakan alat kontrasepsi IUD.Simpulan : terdapat hubungan menggunkan alat kontrasepsi IUD dengan tingkat kenyamanan melakukan hubungan seksual. Petugas kesehatan khusunya perawat agar dapat lebih meningkatkan keterampilan melalui literatur terbaru, pelatihan serta konseling pada setiap pemeriksaan ibu dengan pengguna alat kontrasepsi IUD sehingga memiliki pengetahuan tentang efek dari penggunaan alat kontrasepsi IUD.